Cosmetic outcomes following transoral versus transcervical thyroidectomy. Issue 11 (6th August 2020) - Chen, Lena W.; Razavi, Christopher R.; Hong, Hanna; Fondong, Akeweh; Ranganath, Rohit; Khatri, Surya; Mydlarz, Wojciech K.; Mathur, Aarti; Ishii, Masaru; Nellis, Jason; Shaear, Mohammad; Tufano, Ralph P.; et al.
Abstract: Background: Central neck scars following thyroidectomy can negatively impact patient quality of life. Transoral endoscopic thyroidectomy can reduce postoperative cosmetic burden. Methods: Prospective cohort study of patients seen between June 2018 and January 2019. Scar cosmesis was determined using the validated Scar Cosmesis Assessment and Rating (SCAR) scale and a Visual Analog Scale (VAS) measuring color, contour, and irregularity. Results: Eighty‐one patients (80% female, mean age 43.7 years) were analyzed, with 60% and 40% receiving transcervical and transoral thyroidectomy. Median time from surgery was 3.4 (range: 1‐37.1) weeks. Mean SCAR score was greater for transcervical recipients (4.69 vs transoral 0.99, P  < .001), indicating worse cosmesis. Mean surgeon‐rated total VAS score was similarly increased for transcervical recipients (72.84 vs transoral 16.73, P  < .001). Interrater reliability for both SCAR and total VAS scores was excellent (intraclass correlation 0.93; 95% CI: 0.90‐0.95 for both). Conclusion: Transoral thyroidectomy provides significantly enhanced early cosmesis over the transcervical approach.